Kendala dalam Proses Pembelajaran Keterampilan Berbicara Siswa Kelas IX MTs Syaikh Zainuddin Atsani NW Sesela Tahun Pelajaran 2024/2025 - Nufus, Hidayatun; Setiyadi, DB Putut; Adawiyah, Rabiyatul; Hersulastuti, Hersulastuti; Tukiyo, Tukiyo (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the speaking learning process and identify the obstacles faced by students in speaking lessons in the ninth grade. The research method used is qualitative with a descriptive approach, involving 20 students as research subjects. This study employs a descriptive method. The data sources for this research consist of interview results, observations, and written archives. The informants include teachers, school principals, and students. Data validity testing was carried out using source triangulation, method triangulation, and informant review. Data analysis was conducted using an interactive analysis model. The research results indicate that speaking lessons are still teacher-centered, with monotonous and less varied methods, leading to low student participation. Students tend to feel shy and lack confidence when asked to speak in front of the class. The challenges faced include a lack of engaging learning media, as well as internal and external factors that affect students' speaking abilities. This research provides recommendations to improve students' speaking skills through more interactive and creative learning methods, as well as support from the family and school environment.